Highly sensitive persons feel more emotionally lonely than the general population - Filip Meckovsky; Lukas Novak; Zdenek Meier; Peter Tavel; Klara Malinakova (Scientific Reports)
Abstract This study aimed to investigate the relationship between sensory processing sensitivity (SPS), emotional and social loneliness and social isolation. Data were collected from September 2022 to May 2023 on a sample of 3247 participants aged 18 to 80 (mean age = 31.9 years ± 13.2; 66.2% female). We measured SPS using the Sensory Processing Sensitivity Questionnaire (SPSQ), loneliness using the De Jong Gierveld Loneliness Scale (DJGLS), and social isolation, Neuroticism and Extraversion with the Big Five Inventory. Data analysis was performed using linear regression, binary logistic regression, the t-test, the Chi-square test and ANOVA. In our study, lower SPS was observed especially among men, pensioners and graduates of secondary vocational schools. SPS was associated with emotional loneliness (t = 4.276; b = 0.074; adjusted R2 = 0.181; p < 0.001), but no significant relationship was found between SPS and social loneliness. SPS is associated with higher emotional but not social loneliness or social isolation. Highly Sensitive Persons (HSPs) appear to have a higher need for intimacy and understanding in close relationships, which is essential to know for them, their friends, families and therapists.